2004
DOI: 10.1080/10242690320001608908
|View full text |Cite
|
Sign up to set email alerts
|

Does defence expenditure deter economic growth in Turkey? A cointegration analysis

Abstract: This paper investigates a series of unit root, cointegration and causality tests to ascertain the direction of causality between the growth of GNP and defence expenditure in Turkey for the years 1955-2000. The main conclusion is that there is a long-run equilibrium relationship between GNP and defence expenditures. Furthermore, the short run causality test indicates that there is a unidirectional causality between variables, from defence expenditure to economic growth. In order to see the effect of a shock, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 12 publications
6
25
0
4
Order By: Relevance
“…Moreover, results have indicated negative effect of military spending on economic growth for Pakistan's economy. These findings are consistent with the existing literature such as Khilji and Mahmood (1997), Atesoglu (2002), Karagol and Palaz (2004), Smith and Tuttle (2008), Tang (2008) and Keller et al (2009). The estimated coefficient of government non-military spending is showing positive impact on economic growth supporting the views of Halicioglu (2004), Yildirim et al (2005) and Wijeweera and Webb (2009).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 82%
See 3 more Smart Citations
“…Moreover, results have indicated negative effect of military spending on economic growth for Pakistan's economy. These findings are consistent with the existing literature such as Khilji and Mahmood (1997), Atesoglu (2002), Karagol and Palaz (2004), Smith and Tuttle (2008), Tang (2008) and Keller et al (2009). The estimated coefficient of government non-military spending is showing positive impact on economic growth supporting the views of Halicioglu (2004), Yildirim et al (2005) and Wijeweera and Webb (2009).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 82%
“…At this point, we can compare our results with Khilji and Mahmood (1997) who reported inverse impact of military spending on economic growth. Our empirical evidence are in line with the findings by studies such as Atesoglu (2002) for the USA, Karagol and Palaz (2004) for Turkey, Smith and Tuttle (2008) for the USA and Keller et al (2009) for OECD countries who found inverse relationship between defence spending and economic growth. The impact of non-military spending on economic growth is positive and it is statistically significant at 1% level of significance.…”
Section: Empirical Estimationsupporting
confidence: 81%
See 2 more Smart Citations
“…The feedback perspective explains that both government military expenditure and economic growth affect each other. In the long run, both military expenditure and economic growth were found to have influenced each other in Turkey (Karagol and Palaz, 2004). Kollias et al (2007) however discovered that both military spending and economic growth influenced each other in the long run in all the EU15 group of countries.…”
Section: Introductionmentioning
confidence: 99%